PERBEDAAN PENGETAHUAN PEMELIHARAAN KESEHATAN GIGI SEBELUM DAN SESUDAH DIBERIKAN PENYULUHAN PADA SISWA KELAS III SDN 12 SESETAN TAHUN 2020 - I Nyoman Gejir; I Gusti Agung Alit Hartati; Ni Nengah Sumerti; Maria Martina Nahak (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2020)
Health educational is one of efforts to increase the public behavior. The elementary school students are a group with susceptible in dental and oral diseases. One of efforts to increase the knowledge of students is elucidation of health, belong to dental and oral health. The objectives of this study is to know the differential of the knowledge about dental care before and after elucidation in the students in third level in SDN 12 Sesetan in 2020. This research is pre experimental study, with pre and post test design, which done in May 2020, with 35 respondents. The data is collected with questionnaire. The results of this research shows that, before elucidation shows that : 54,29% (Very Good Criteria), and 2,85% (Failure Criteria), the average of the knowledge about dental health is 76 (Good Criteria). After elucidation, shows that : 100% (Very Good Criteria) and the average of the knowledge about dental health is 92,57 (Very Good Criteria). The results analysis with sign test shows that there is differential of knowledge about dental health care between before and after elucidation in the students in third level in SDN 12 Sesetan in 2020. The conclusion of this research are, before elucidation the average of the knowledge about dental health is in Good Criteria, and after elucidation is in Very Good Criteria. There is differential of knowledge about dental health care between before and after elucidation in the students in third level in SDN 12 Sesetan in 2020.